PENGARUH KONFLIK KERJA DAN STRES KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN SIANTAR SIMALUNGUN - Yohana Lasmaria Panggabean; Darwin Lie; Efendi Efendi; Fitria Halim (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2019)
Result of analysis from linear regresi modestly that is Ŷ = 107,279–0,374X1+0,497X2, meaning there are negative influence between Work Conflict and to Job Stress to performance of employee in Kantor Kecamatan Siantar Simalungun. The strength of relationship between the variables is very strength, that is r= 0,468. From coefficient determinasi can explainable high and low of customer’s purchase decision 21,9 %, and the res78,1 % explained by other factor which is not discussed in this research. From result of processing and calculation questionnaires, writer get the conclusion that Work Conflict and Job stress at Kantor Kecamatan Siantar Simalungun have an effect on to performance of employee. This matter is proved by hypothesis test either simultaneously where result test the Fhitung(5,185)> Ftabel (3,25) and which significant 0,010< ɑ 0,05.Keywords: Work Conflict, Job Stress, and The Performance of Employee